M6A-Atlas: a comprehensive knowledgebase for unraveling the N6-methyladenosine (m6A) epitranscriptome. Issue Volume 49:Issue D1(2021) (21st August 2020) - Tang, Yujiao; Chen, Kunqi; Song, Bowen; Ma, Jiongming; Wu, Xiangyu; Xu, Qingru; Wei, Zhen; Su, Jionglong; Liu, Gang; Rong, Rong; Lu, Zhiliang; de Magalhães, João Pedro; et al.
Abstract: N 6 -Methyladenosine (m 6 A) is the most prevalent RNA modification on mRNAs and lncRNAs. It plays a pivotal role during various biological processes and disease pathogenesis. We present here a comprehensive knowledgebase, m 6 A-Atlas, for unraveling the m 6 A epitranscriptome. Compared to existing databases, m 6 A-Atlas features a high-confidence collection of 442 162 reliable m 6 A sites identified from seven base-resolution technologies and the quantitative (rather than binary) epitranscriptome profiles estimated from 1363 high-throughput sequencing samples. It also offers novel features, such as; the conservation of m 6 A sites among seven vertebrate species (including human, mouse and chimp), the m 6 A epitranscriptomes of 10 virus species (including HIV, KSHV and DENV), the putative biological functions of individual m 6 A sites predicted from epitranscriptome data, and the potential pathogenesis of m 6 A sites inferred from disease-associated genetic mutations that can directly destroy m 6 A directing sequence motifs. A user-friendly graphical user interface was constructed to support the query, visualization and sharing of the m 6 A epitranscriptomes annotated with sites specifying their interaction with post-transcriptional machinery (RBP-binding, microRNA interaction and splicing sites) and interactively display the landscape of multiple RNA modifications. These resources provide fresh opportunities for unraveling the m 6 A epitranscriptomes. m 6 A-Atlas is freely accessible at: www.xjtlu.edu.cn/biologicalsciences/atlas .